2017
DOI: 10.1038/srep41879
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitory role of Arg-84 in anion channelrhodopsin-2 expressed in Escherichia coli

Abstract: Anion channelrhodopsin-2 (ACR2) was recently identified from the cryptophyte algae Guillardia theta and has become a focus of interest in part because of its novel light-gated anion channel activity and its extremely high neural silencing activity. In this study, we tried to express ACR2 in Escherichia coli cells as a recombinant protein. The E. coli cells expressing ACR2 showed an increase in pH upon blue-light illumination in the presence of monovalent anions and the protonophore carbonyl cyanide m-chlorophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…By taking advantage of the expression system, we performed mutational analysis on the conserved “basic” amino acid residues among ACRs, and found that the positive charge of R84 located at the extracellular side plays an inhibitory role in its anion transport activity ( Fig. 1C ) [ 25 ], although the precise position and the interaction remain unknown. The prediction of protein structure by molecular simulation and informatics is still developing.…”
mentioning
confidence: 99%
“…By taking advantage of the expression system, we performed mutational analysis on the conserved “basic” amino acid residues among ACRs, and found that the positive charge of R84 located at the extracellular side plays an inhibitory role in its anion transport activity ( Fig. 1C ) [ 25 ], although the precise position and the interaction remain unknown. The prediction of protein structure by molecular simulation and informatics is still developing.…”
mentioning
confidence: 99%
“…Although the secondary Cl − binding site has not been identified yet, we estimate that it is located near or along the Cl − conducting pathway in the protein. Previously, the inhibitory role of the Arg residue on the extracellular surface of Gt ACR2, which is a candidate consisting of the Cl − conducting pathway, for its anion channel function has been reported 8 . One of the authors’ discussion points regarding the inhibition mechanism is that the positively charged Arg84 interacts with the negatively charged Cl − , which prevents the Cl − from being transported through the protein 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the inhibitory role of the Arg residue on the extracellular surface of Gt ACR2, which is a candidate consisting of the Cl − conducting pathway, for its anion channel function has been reported 8 . One of the authors’ discussion points regarding the inhibition mechanism is that the positively charged Arg84 interacts with the negatively charged Cl − , which prevents the Cl − from being transported through the protein 8 . Together with the fact that Psu ACR1 conserves the corresponding residue as Arg84, we estimate that the inhibitory role of Arg84 is related to the secondary Cl − binding and therefore the Arg84 in Psu ACR1 is one candidate for the secondary Cl − binding site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural ACRs showed a larger (several nA) photocurrent and a stronger inhibition of the generation of action potential by light than those of ChR-based anion channels (Govorunova et al 2015). We recently demonstrated that the ion transport activity of GtACR2 is strongly (10-fold) enhanced by a mutation of the conserved Arg residue (R84E) located on a loop (the B-C loop) between TM helix 2 and TM helix 3, when it is expressed in Escherichia coli cells as a recombinant protein (Doi et al 2017). In the future, further modification(s) will be applied to natural ACRs to obtain efficient neural silencers.…”
Section: Conversion Of Cation Channelsmentioning
confidence: 99%